2018
DOI: 10.1111/zph.12442
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Salmonella Typhimurium associated with feeder rodents

Abstract: In December 2012, an increase in human Salmonella Typhimurium cases was identified in the province of Ontario, Canada launching an outbreak investigation. The outbreak spanned 3 years (2012-2014), with 134 cases reported from five Canadian provinces. There was a substantial burden of illness among children: 45% of cases were children 12 years old or under, and 23% of cases were under 5 years old. Epidemiologic, traceback and laboratory findings linked this outbreak to feeder rodents (used to feed snakes) suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Particular attention has recently been given to snakes and lizards, as human interaction with these reptiles has become increasingly common in domestic environments (11,60). In this sense, it is important to highlight that these reptiles are mainly fed with food from animal origin, which represents an important source of Salmonella (49,61,62). Previous studies carried out in the United Kingdom reported the important role of commercial feeder rodents in bacterial transmission among reptiles, and even their owners (63,64).…”
Section: Discussionmentioning
confidence: 99%
“…Particular attention has recently been given to snakes and lizards, as human interaction with these reptiles has become increasingly common in domestic environments (11,60). In this sense, it is important to highlight that these reptiles are mainly fed with food from animal origin, which represents an important source of Salmonella (49,61,62). Previous studies carried out in the United Kingdom reported the important role of commercial feeder rodents in bacterial transmission among reptiles, and even their owners (63,64).…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, previous reports have shown that shedding of Salmonella spp. is greater in carnivore reptiles fed by contaminated reptile feeder mice [46]. In fact, feeder rodents are potential carriers of Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…In cases involving pet turtles, almost half (45%) of infections occurred in children younger than 5 years [180]. Salmonella infections are often transferred by feeder rodents [181] and outbreaks highlight the importance of improving public awareness and education in countries who receive imported reptiles [182]. It is advised to exclude reptiles, amphibians, rodents, exotic species, baby poultry, and raw animal-based pet food items from the households of patients at high risk.…”
Section: Keeping Unusual Exotic Animalsmentioning
confidence: 99%